Long-term follow-up of patients with chronic hepatitis C with sustained virologic response to interferon - Ferreira,Sandro da Costa (2010)
BACKGROUND AND AIM: The durability of the sustained virologic response (SVR) in patients with chronic hepatitis C after treatment and the ideal follow-up time for these patients remains undefined. The objective of the study was to evaluate the durability of the virologic response in patients with chronic hepatitis C followed up for at least 12 months after SVR at HCFMRP-USP. METHODS: The study was conducted on 174 patients with chronic hepatitis C treated with different antiviral regimens who had achieved SVR. Qualitative serum HCV-RNA was determined by the commercial kit (COBAS AMPLICOR HCV, v2.0). RESULTS: There was predominance of male (73%) with a mean age of 45.6 ± 10 years. Liver cirrhosis was present in 16.1% of the study subjects. Mean follow-up time after SVR was 47 months (12-156 months). Twenty-two patients received monotherapy with interferon; 94 received interferon plus ribavirin, and 58 received pegylated interferon plus ribavirin. A total of 134 patients (77.0%) received one treatment course, 29 (16.7%) received two courses, and 11 (6.3%) received three courses. The distribution of HCV genotypes was: genotype 1 (40.2%), genotype 3 (40.8%) and genotype 2 (10.3%). Genotype was undetermined in 8.7% of cases. None of the 174 patients had recurrence of HCV infection. Two cirrhotic patients developed hepatocellular carcinoma (HCC) during follow-up. CONCLUSIONS: Among patients with SVR there was no recurrence of HCV infection or evidence of liver disease progression in any patient followed up for a mean of 47 months after SVR, except for patients with advanced hepatic disease before treatment, who may develop HCC despite SVR. Therefore, one can assume that SVR is associated with long term good prognosis.